Update on schistosomiasis mansoni in Brazil: an integrative review (Research, Society and Development, 2023)
The present work performs an integrative review of the literature on schistosomiasis in Brazil, a parasitic and waterborne disease caused by flatworms of the genus Schistosoma (S. mansoni; S. japonicum; S. haematobium), and which still manifests itself as a problem significant public health problem in this country. It aims to highlight clinical data, as well as epidemiological data, presenting the most affected regions, individuals most vulnerable to infection and factors associated with its occurrence. In addition, it aims to update the current scenario with regard to the development of a vaccine against the parasites that cause schistosomiasis. The study carried out analyzes in the PubMed and Latin American and Caribbean Literature in Health Sciences (LILACS), ScienceDirect databases, as well as using data from the World Health Organization (WHO), the Centers For Disease Control and Prevention (CDC) and the Ministry of Health of Brazil (MS). It is concluded that schistosomiasis remains a disease of high national relevance, since it still manifests itself as a public health problem, responsible for intensifying situations of social inequality and having a direct connection with poverty, as a cause, but also as a consequence of same. Currently, several vaccines are in the clinical trial phase, but none is commercially available, and investment in research is of great importance.